Fiscal decentralization to rural governments in India - Sethi, Geeta (New Delhi : Oxford University Press, 2004)
with special references to Karnataka and Kerala
Includes statistical tables
Bibliography: p. [209] - 215
Keywords: International Bank for Reconstruction and Development, Washington, D.C.; Fiscal policy -- India; Decentralization in government -- India Economic aspects; Rural development -- India; Finance, Public -- India; India -- Econmic policy